Analisis Pengaruh Tingkat Pendapatan Dan Investasi Terhadap Profitabilitas Pada Perusahaan Startup - widiyohening, caecilia rosma (Politeknik Sawunggalih Aji, 2025)
Profitability is a company’ability to generate profits from investment and income that has been generated within a certain period of time. This study aims to examine the ability of variables to produce . The variables used in this study are income, investment and profitability. The data used in this study are financial reports from e-commerce and technology sector companies listed on the Indonesia Stock Excange in the 2020-2023 period with recorded population of 21 registered companies. The technique used to determine the research sample is purposive sampling. This study uses multiple linear regression analysis.This results showed that the income variable and the investment variable both had a positive and significant effect on profitability..